WAIS Divide Snowpit Chemical and Isotope Measurements, Antarctica - Koffman, Bess; Kreutz, Karl (IEDA: US Antarctic Program Data Center, 2011)
This dataset includes major ion, trace element, microparticle and oxygen isotope (δ18O) data for a snowpit dug and sampled in December 2008 near the West Antarctic Ice Sheet (WAIS) Divide ice core site. The pit was dug approximately 4 km upwind from the drilling arch in the clean air sector of camp. Sampling was done using trace element clean techniques and all depths are in water equivalents. Data are available via FTP in ASCII text (.txt) format.